If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(10 + -2b) + b = 6 (10 * 2 + -2b * 2) + b = 6 (20 + -4b) + b = 6 Combine like terms: -4b + b = -3b 20 + -3b = 6 Solving 20 + -3b = 6 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -3b = 6 + -20 Combine like terms: 20 + -20 = 0 0 + -3b = 6 + -20 -3b = 6 + -20 Combine like terms: 6 + -20 = -14 -3b = -14 Divide each side by '-3'. b = 4.666666667 Simplifying b = 4.666666667
| 7x+6=6x-2 | | 7x-5x-3=6 | | (-4)+(-6)(+4)-(-1)= | | 3k*t-k=3k | | 3*7+4h=7 | | -2x^2+4=x^2+x-7 | | 2a+a-5=5 | | 0.5x+8=6 | | 4*4-2(-6)(-2)/(15+3*3)=x | | y-60=6(x-10) | | -(6y+5)-(-5y-7)=-6 | | z^2-1000x+60775=0 | | 2x+35/4=5 | | 4x+2*5-3x=1 | | 4*4=x | | 4*4=4*4 | | 13x-2y=-5 | | 9x+8=x | | 16=-2z | | 23t-8t^2=-3 | | 5-c/6=d-7c | | 3.5x+3.5x=-21 | | 15=-16t^2+30t+5 | | 25w^2-30w+9= | | -2(6x-8)+4=20 | | 4x+7x-15=0 | | q-3r=2r | | -6x+8y=-4 | | 4-8n=10 | | 4x+6x+4=0 | | 8+2r-4=9r+4-6r | | 5y+12=27 |